Irreversible mass loss of Canadian Arctic Archipelago glaciers. Issue 5 (7th March 2013) - Lenaerts, Jan T. M.; van Angelen, Jan H.; van den Broeke, Michiel R.; Gardner, Alex S.; Wouters, Bert; van Meijgaard, Erik
Abstract: [1] The Canadian Arctic Archipelago (CAA) contains the largest volume of glacier ice on Earth outside of Antarctica and Greenland. In the absence of significant calving, CAA glacier mass balance is governed by the difference between surface snow accumulation and meltwater runoff—surface mass balance. Here we use a coupled atmosphere/snow model to simulate present‐day and 21st century CAA glacier surface mass balance. Through comparison with Gravity Recovery and Climate Experiment mass anomalies and in situ observations, we show that the model is capable of representing present‐day CAA glacier mass loss, as well as the dynamics of the seasonal snow cover on the CAA tundra. Next, we force this model until 2100 with a moderate climate warming scenario (AR5 RCP4.5). We show that enhanced meltwater runoff from CAA glaciers is not sufficiently compensated by increased snowfall. Extrapolation of these results toward an AR5 multimodel ensemble results in sustained 21st century CAA glacier mass loss in the vast majority (>99%) of the ~7000 temperature realizations. Key Points: RACMO2 is capable of simulating present‐day CAA mass loss Increase of meltwater runoff is not compensated by increased snowfall Persistent 21 century glacier mass loss in nearly all AR5 projections